Influence of pharmacists' opinions on their dispensing medicines without requirement of a doctor's prescription - Francisco Caamaño; Manuel Tomé-Otero; Bahi Takkouche; Juan Jesús Gestal-Otero (Elsevier, 2005)
Objective: To assess the influence of pharmacists' opinions on their dispensing medicines with a «medical prescription only» label without requiring a doctor's prescription. Methods: We performed a cross-sectional study of 166 community pharmacies in northwest Spain. The opinions of pharmacists on the following were collected as independent variables through personal interview: a) physicians' prescribing practices; b) the pharmacist's qualifications to prescribe; c) the responsibility of the pharmacist regarding the dispensed drugs; d) the customer' qualifications for self-medication; and e) the pharmacist's perception of his or her own work. The dependent variable was the pharmacist's demand for a medical prescription for 5 drugs, which in Spain require a prescription. Multiple linear regression models were constructed. Results: The response rate was 98.8%. A total of 65.9% of pharmacists reported dispensing antibiotics without a prescription. This percentage was 83.5% for nonsteroidal anti-inflammatory drugs, 46.3% for angiotensin-converting enzyme inhibitors, 13.4% for benzodiazepines, and 84.8% for oral contraceptives. Further results showed that pharmacists with a heavier workload and those who underestimated the physicians' qualifications to prescribe but overestimated their own qualifications to prescribe less frequently demanded medical prescriptions. In contrast, pharmacists who stressed the importance of their duty in rationalizing the consumption of drugs more frequently demanded medical prescriptions. Conclusion: Our results suggest that to increase the quality of dispensing: a) the importance of the pharmacist's duty in controlling drug consumption should be stressed; b) pharmacies' workload should be optimized; and c) perceptions of physicians' prescribing practices among pharmacists should be improved. Objetivo: Evaluar la influencia de las opiniones de los farmacéuticos que no solicitan receta médica para dispensar fármacos que la requieren para su venta. Métodos: Se ha llevado a cabo un estudio transversal sobre una muestra de 166 farmacéuticos de oficina de farmacia en la provincia de A Coruña. Las opiniones de los farmacéuticos, variables e independientes, fueron medidas mediante entrevista personal. Se valoraron las opiniones siguientes: a) prácticas prescriptoras de los médicos; b) cualificación de los farmacéuticos para prescribir; c) la responsabilidad de los farmacéuticos sobre los medicamentos dispensados; d) la cualificación de los clientes para automedicarse, y e) la percepción de los farmacéuticos sobre su trabajo. La exigencia de receta por parte del farmacéutico para 5 fármacos, que en España deben dispensarse con receta, fue la variable dependiente que se tuvo en cuenta. Se construyeron modelos de regresión múltiple. Resultados: La participación fue del 98,8%. Un total del 65,9% de los farmacéuticos afirmaron dispensar antibióticos sin receta. Este porcentaje fue del 83,5% para los antiinflamatorios no esteroideos, 46,3% para los inhibidores de la enzima de conversión de la angiotensina, 13,4% para las benzodiazepinas y 84,8% para los anticonceptivos orales. Además, los resultados muestran que los farmacéuticos con mayor carga de trabajo y los que califican peor la prescripción de los médicos, y que en mayor medida consideran que ellos mismos están capacitados para prescribir, exigen menos recetas médicas. Por el contrario, los farmacéuticos que otorgan mayor importancia a la racionalización en el consumo de fármacos exigen receta más frecuentemente. Conclusión: Nuestros resultados indican que para el incremento en la calidad de la dispensación el sistema debería lograr: a) incrementar la importancia que los farmacéuticos otorguen al control y la racionalización del consumo de fármacos; b) adecuar la carga de trabajo de las farmacias, y c) mejorar la percepción que los farmacéuticos tienen de las pautas prescriptoras de los médicos.